Methicillin-resistant Staphylococcus aureus nasal colonization in people living with HIV and healthy people in Kathmandu, Nepal - Samjhana Kapali; Anil Pokhrel; Anup Bastola; Reshma Tuladhar; Dev Raj Joshi (Future Science OA)
Aim: This study aimed to compare methicillin-resistant Staphylococcus aureus (MRSA) nasal colonization in people living with HIV (PLHIV) and healthy people from Kathmandu. Methods: MRSA isolated from 400 nasal swabs was screened using a cefoxitin disc and confirmed by the presence of the mecA gene. Results: MRSA nasal carriers among the PLHIV and control cohorts were 3.5% (7 out of 200) and 5.0% (10 out of 200), respectively. All the MRSA from PLHIV and most of MRSA from healthy controls were PVL positive. Longer duration of antiretroviral therapy significantly reduces the risk of MRSA nasal colonization in PLHIV. Conclusion: There is no significant difference in MRSA nasal colonization in PLHIV and healthy controls in this study region.